Research on Ecological Restoration Mechanism of Rare-Earth Mines Based on Evolutionary Game - Guangli Yan; Fei Xue; Zhongxue Li (Advances in Materials Science and Engineering)
With the continuous improvement of the rare earth’s international status, the status of rare Chinese earth has gradually become prominent all over the world. When China enjoys the advantages of large reserves of rare-earth resources, at the same time, Chinese rare-earth enterprises are lagging in technology and lacking innovation capabilities. The rare-earth industry is mainly concentrated on the separation and smelting process, which has an indelible impact on the ecological environment around the mine. Some scholars have carried out research on ecological restoration in mining areas, but there are few studies on interest subjects in ecological restoration work in mining areas, especially the research based on game theory is more scarce. This article constructs a trilateral evolutionary game model of the central, local governments, and mining enterprises. This article analyzes the impact mechanism of policy changes on the rare-earth mining industry and analyzes the three-party evolutionary game model by adjusting the values of external variables. The research shows that the central government’s subsidies to local enterprises, the central government’s performance evaluation to the government, the local government’s punishment to enterprises, and the local enterprise’s reproduction income are important factors that determine the evolution of the trilateral game. Therefore, the central government should strengthen the supervision of local governments and enterprises when formulating policies related to the rare-earth industry, and local governments should strengthen their own management and local environmental regulations.